2007
DOI: 10.1097/phm.0b013e31806de721
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Walking Tests in People with Claudication

Abstract: Both the 6MW and the SWT are reliable walking tests for claudicant patients. However, the reliability coefficients obtained with the SWT are higher, the measurements are less variable, and there were better associations between this walking test and hemodynamic variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
1
29
0
2
Order By: Relevance
“…22 The expected ICC was consistent with the mean ICC for the ISWD as verified in 7 previous studies that tested its reliability (range 0.80 -0.99). 13,[23][24][25][26][27][28] Variance analysis comparing the ISWD and the cardiorespiratory and metabolic responses between the second and third ISWT was performed with a paired t test or its corresponding nonparametric test, the Wilcoxon test.…”
Section: Discussionmentioning
confidence: 99%
“…22 The expected ICC was consistent with the mean ICC for the ISWD as verified in 7 previous studies that tested its reliability (range 0.80 -0.99). 13,[23][24][25][26][27][28] Variance analysis comparing the ISWD and the cardiorespiratory and metabolic responses between the second and third ISWT was performed with a paired t test or its corresponding nonparametric test, the Wilcoxon test.…”
Section: Discussionmentioning
confidence: 99%
“…A large discrepancy has been reported between walking ability and claudication walking distances as measured on a treadmill, [2][3][4] implying that treadmill assessments may not be representative of daily life walking ability. Alternative more simple tests include a 6-minute walking test, 16,54 a shuttle walkingtest, 16,45 a PADHOC device, 22 and a global positioning system (GPS) device. 55 Furthermore, a simple questionnaire like the Walking Impairment Questionnaire (WIQ) could be used in properly designed trials.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 The SWT was chosen due to its standardization, less influence as to patient encouragement, advantages to develop ground walking at incremental speeds, besides presenting more stability in reproducibility measurements. 13 McDermontt et al suggested that the ABI measured after physical activity could potentially have better correlation levels with performance than the ABI-r, since individuals with POAD could have a fall of more than 25% in ABI-e. 5,14 In the present study, there was a reduction of around 36% in the index obtained after effort, but there was no substantial correlation between this index and measures of time, speed or distance of symptom onset or limiting symptom. Correlation between ABI-r and functional variables was small and not significant.…”
Section: Discussionmentioning
confidence: 99%